The decrease of fibroblasts and fibroblast growth factor-2 expressions as a result of X-ray irradiation on the tooth extraction socket in Rattus novergicus - Fatma Yasmin Mahdani; Intan Nirwana; Jenny Sunariani (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Wound healing involves cellular, molecular, physiological, and biochemical processes as responses to tissue damage. For instance, when a failure during tooth extraction occurs, radiographic examination, X-rays, is required. X-rays as an enforcer diagnosis can damage DNA chain, resulting in cell death and inhibition of wound healing process. Purpose: This research aims to analyze fibroblasts cell number and fibroblast growth factor-2 (FGF-2) expressions during wound healing process after tooth extraction as a result of X-ray irradiation. Methods: There were three research groups, each consisting of ten rats. Incisor tooth extraction was performed on the left lower jaw, and then X-ray examination was conducted at certain irradiation doses, namely 0 mSv, 0.08 mSv, and 0.16 mSv. Those animals were sacrificed on day 3, and on day 7 after the extraction, histopathology and immunohistochemistry examinations were conducted to determine fibroblast cell number and FGF-2 expressions. Data obtained were then analyzed by oneway ANOVA and Tukey HSD tests. Results: The number of fibroblasts decreased significantly in the group with the irradiation dose of 0.16 mSv applied on day 7 after the extraction (p <0.05). Similarly, the number of FGF-2 expressions decreased significantly in the group with the irradiation dose of 0.16 mSv applied on days 3 and 7 after the extraction (p <0.05). Conclusion: X-ray irradiation at a dose of 0.16 mSv can inhibit the healing process of tooth extraction wound due to the decreasing of fibroblasts cell number and FGF-2 expressions.